What Every First Year Female Law Student Should Know - Torrey, Morrison; Ries, Jennifer; Spiliopoulous, Elaine (Columbia Journal of Gender and Law, 1998)
What can first-year women law students expect during law school? Is law school still dominated by men or has legal education responded to the challenge to eliminate sex discrimination?’ Is there anything women can do to minimize the effects of gender bias and maximize their law school experience? These are the questions addressed in this article. Unfortunately, numerous studies now have documented what the co-authors already knew from personal experience-women can expect a hostile environment while attending law school.